Regional cerebral hypoperfusion after acute sleep deprivation: A STROBE-compliant study of arterial spin labeling fMRI. Issue 2 (January 2019) - Zhou, Fuqing; Huang, Muhua; Gu, Lili; Hong, Shunda; Jiang, Jian; Zeng, Xianjun; Gong, Honghan
Abstract : Abstract: Previous neuroimaging studies have shown that functional changes occur after acute sleep deprivation, which suggest detrimental effects of a lack of sleep on the intrinsic functional architecture of the brain. We aimed to identify regional resting perfusion changes in subjects with acute sleep deprivation. Thirty-three healthy subjects with habitual good sleep participated in 36 hours (2 days and 1 night) of sleep deprivation and then underwent the attention network test and pseudo-continuous arterial spin labeling scanning. Regional cerebral blood flow was used to compare cerebral perfusion before and after sleep deprivation. Correlation analyses of regional perfusion changes and scores on the attention network test were performed. Compared with the baseline (n = 20) scans, the scans of subjects after sleep deprivation (n = 26) revealed a slower response time (549.99 milliseconds vs 603.36 milliseconds; t  = −2.301; P  = .028) and a significantly higher lapse rate (0.88% vs 22.85%; t  = −2.977; P  = .006). The sleep deprivation subjects showed lower cerebral blood flow (CBF) in the left parahippocampal gyrus/fusiform cortex (pHipp/Fus), right pHipp/Fus, and right prefrontal cortex (PFC) relative to the baseline subjects (Gaussian random field correction, voxel level P  < .01, and cluster level P  < .05). Although no significant relationships were observed between the altered regional CBF (rCBF) values and the attention network test scores, the receiver-operating characteristic and leave-one-out cross-validation analyses revealed that significant decreases in rCBF in the bilateral pHipp/Fus and right PFC could discriminate between sleep deprivation and good sleep status. We observed that rCBF was reduced after 36 hours (2 days and 1 night) of sleep deprivation. Our preliminary findings suggest an acute vulnerability to hypoperfusion due to lack of sleep.